PENGEMBANGAN OBJEK WISATA EMBUNG KLEDUNG DENGAN KONSEP EKOWISATA - Ardiana Yuli Puspitasari; Tjoek Suroso Hadi; Wa Ode Sitti Khasanah Ramli (Universitas Islam Sultan Agung Semarang, 2021)
ABSTRACTOne area that has tourism potential is Kledung District, Temanggung Regency. According to the Regional Tourism Development Master Plan (RIPPDA) of Temanggung Regency in 2012, this area is included in the Regency Strategic Tourism Area (KSPK) of Kledung and its surroundings with the theme of the Sindoro Sumbing foot tourism. Given the location and geographical position which is on the main tourist route of Yogya - Borobudur - Dieng, this is an indication of the great potential for Kledung Village in tourism development. One of the tourist objects in Kledung Village is Embung Kledung. With a panoramic view of the natural scenery of mountains and very beautiful waters and the surrounding biodiversity, this area is very potential to be developed as a tourist attraction. However, the problems that occur are limited access from the main road to tourist objects and limited supporting facilities for tourist objects. With the increasing number of visitors, a more efficient, precise, and sustainable direction for the use of space is needed to preserve nature as its main attraction. This study aims to provide directions/alternatives for the development of the Embung Kledung Tourism Object based on ecological tourism (ecotourism) which maintains natural preservation as its main attraction but can provide economic and social benefits for the local community. With a mixed research methodology, it produces several things: 1). The Ecotourism concept that is applied takes into account 5 (five) elements, namely, environment, community, education and experience, sustainability, and management; 2). Priority infrastructure needs are circulation arrangement, additional electricity capacity, waste handling, and waste management; 3) Four clusters development were found and 28 types of facilities were required.Keywords: Embung Kledung, Ecotourism Concept, Tourism Object Development.ABSTRAKSalah satu daerah yang memiliki potensi pariwisata adalah Kecamatan Kledung, Kabupaten Temanggung. Menurut Rencana Induk Pengembangan Pariwisata Daerah (RIPPDA) Kabupaten Temanggung Tahun 2012 wilayah ini termasuk dalam Kawasan Strategis Pariwisata Kabupaten (KSPK) Kledung dan sekitarnya dengan tema wisata alam kaki Sindoro Sumbing. Mengingat letak dan posisi geografisnya yang berada pada jalur wisata utama Yogya – Borobudur – Dieng, menjadi indikasi potensi besar bagi Desa Kledung dalam pengembangan pariwisata. Salah satu objek wisata di Desa Kledung adalah Embung Kledung. Dengan tawaran panorama pemandangan alam pegunungan dan perairan yang sangat indah serta keanekaragaman hayati di sekitarnya menjadikan kawasan ini sangat potensial untuk dikembangkan sebagai objek wisata. Namun permasalahan yang terjadi adalah keterbatasan akses dari jalan utama menuju objek wisata dan terbatasnya fasilitas pendukung objek wisata. Dengan semakin meningkatnya jumlah pengunjung dibutuhkan arahan pemanfaatan ruang yang lebih efisien, tepat, dan berkelanjutan untuk menjaga kelestarian alam sebagai daya tarik utamanya. Penelitian ini bertujuan untuk memberikan arahan/alternatif pengembangan Objek Wisata Embung Kledung berbasis wisata ekologi (ekowisata) yang tetap menjaga kelestarian alam sebagai daya tarik utamanya tetapi dapat memberi manfaat ekonomi dan sosial bagi masyarakat lokal. Dengan metodologi penelitian campuran, menghasilkan beberapa hal: 1). Konsep Ekowisata yang diterapkan memperhatikan 5 (lima) unsur yakni, lingkungan, masyarakat, pendidikan dan pengalaman, berkelanjutan, dan manajemen; 2). Kebutuhan prasarana prioritas adalah penataan sirkulasi, penambahan kapasitas listrik, penanganan limbah, dan pengelolaan sampah; 3) Ditemukan empat cluster pengembangan yang terbentuk dan perlu dilengkapi 28 jenis fasilitas.Kata Kunci: Embung Kledung, Konsep Ekowisata, Pengembangan Objek Wisata.